2021
DOI: 10.18502/ijph.v50i3.5626
|View full text |Cite
|
Sign up to set email alerts
|

Has COVID-19 Improved Public Awareness on Oral Hygiene?

Abstract: The article's abstract is not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Another study discussed whether COVID-19 has improved public awareness based on information available on Google Trends [22]. It found that following the outbreak of the COVID-19 epidemic, the general public appeared to be more concerned about their dental hygiene, which aligns with our findings [22].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Another study discussed whether COVID-19 has improved public awareness based on information available on Google Trends [22]. It found that following the outbreak of the COVID-19 epidemic, the general public appeared to be more concerned about their dental hygiene, which aligns with our findings [22].…”
Section: Discussionsupporting
confidence: 83%
“…Another study discussed whether COVID-19 has improved public awareness based on information available on Google Trends [22]. It found that following the outbreak of the COVID-19 epidemic, the general public appeared to be more concerned about their dental hygiene, which aligns with our findings [22]. A study conducted in the United States targeted adolescents and young adults to examine their perspectives on dental health and oral hygiene practices [23]; 44% of the survey participants stated that COVID-19 affected their oral health [23].…”
Section: Discussionmentioning
confidence: 99%
“…Since data collection, there has been an unprecedented global health pandemic with older adults showing greater vulnerability to the virus (Wang et al, 2020). The increased spotlight on health due to the COVID-19 pandemic has increased the general public’s motivation to seek out public health information and improve health-related behaviours (Jun et al, 2021; Sorooshian & Kumar, 2021). It would be interesting therefore to explore similar patterns in dementia knowledge since the pandemic.…”
Section: Discussionmentioning
confidence: 99%